Mechanical thinning of fruits and flowers in peach trees - Barreto, Caroline Farias; Navroski, Renan; Benati, Jorge Atilio; Pereira, José Francisco Martins; Malgarim, Marcelo Barbosa; Antunes, Luis Eduardo Correa (Revista de Ciências Agroveterinárias, 2020)
Techniques that improve process efficiency are important to reduce the operational cost of orchards. Two mechanical devices were tested to verify the efficiency of peach tree thinning and the influence on fruit production and quality characteristics. The experiment was conducted using the Maciel cultivar in a commercial orchard in Pelotas, Rio Grande do Sul, Brazil. The treatments consisted of mechanical flower blossom thinning using the Carpa ElectroTM and “trimming” equipment; mechanical fruit thinning using the “trimming” equipment; and manual fruit thinning. The mechanical thinning associated with manual thinning of peach trees may be a viable alternative to manual thinning since it reduces the execution time. Both equipment can be used for mechanical thinning since they didn't change the production per plant, number of fruits per plant, fruit mass, fruit diameter, physicochemical characteristics, and bioactive compounds of the fruits.